2022
DOI: 10.1158/2159-8290.cd-21-1022
|View full text |Cite
|
Sign up to set email alerts
|

IFNα Potentiates Anti–PD-1 Efficacy by Remodeling Glucose Metabolism in the Hepatocellular Carcinoma Microenvironment

Abstract: The overall response rate for anti-PD-1 therapy remains modest in hepatocellular carcinoma (HCC). We found that a combination of interferon alpha (IFN-a) and anti-PD-1-based immunotherapy resulted in enhanced antitumor activity in unresectable HCC patients. In both immunocompetent orthotopic and spontaneous HCC models, IFN-a therapy synergized with anti-PD-1 and the combination treatment led to significant enrichment of cytotoxic CD27+ CD8+ T cells. Mechanistically, IFN-a suppressed HIF1a signaling by inhibiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 70 publications
5
64
0
Order By: Relevance
“…IFN‐α is another protein belonging to the type I IFN family, which is currently used in cancer therapy, and it was thought that the direct inhibitory effects on tumor cell growth/functions were the major mechanisms important in the antitumor response in patients 24 . A combination of IFN‐α and anti‐PD‐1‐based immunotherapy resulted in enhanced antitumor activity in patients with unresectable HCC 25 . In addition, antigen contact with the BCR and subsequent signal transduction are the initial steps for B cell activation and proliferation, 26 and intertumoral B cells located in a tertiary lymphoid structure may contribute to the antitumor activity of immunotherapy 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IFN‐α is another protein belonging to the type I IFN family, which is currently used in cancer therapy, and it was thought that the direct inhibitory effects on tumor cell growth/functions were the major mechanisms important in the antitumor response in patients 24 . A combination of IFN‐α and anti‐PD‐1‐based immunotherapy resulted in enhanced antitumor activity in patients with unresectable HCC 25 . In addition, antigen contact with the BCR and subsequent signal transduction are the initial steps for B cell activation and proliferation, 26 and intertumoral B cells located in a tertiary lymphoid structure may contribute to the antitumor activity of immunotherapy 27 …”
Section: Discussionmentioning
confidence: 99%
“…24 A combination of IFN-α and anti-PD-1-based immunotherapy resulted in enhanced antitumor activity in patients with unresectable HCC. 25 In addition, antigen contact with the BCR and subsequent signal transduction are the initial steps for B cell activation and proliferation, 26 and intertumoral B cells located in a tertiary lymphoid structure may contribute to the antitumor activity of immunotherapy. 27 A heatmap representing the ssGSEA scores of those gene sets showed a clear tendency of VETC+ HCCs to aggregate on the side of lower scores of those immune-related gene sets (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The combined e cacy and safety of immunotherapy and antiangiogenic therapy for unresectable HCC have been con rmed in multiple studies [21]. IFNα and anti-PD1 cotreatment as a novel combination strategy for HCC has also been suggested [10]. A recent study demonstrated that perioperative camrelizumab plus apatinib displays promising e cacy and manageable toxicity in patients with resectable HCC [27].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacologically selective inhibition of PTP1B using MSI-1436 induced the T cell-mediated tumor suppression and enhanced PD-1 blockade response ( 47 ). Moreover, a combination of anti-PD-1-based immunotherapy with IFN-α resulted in encouraging anticancer activity in unresectable HCC patients ( 52 ). In infiltrating CD8 + T cells, IFN-α downregulates the ability to consume glucose and consequentially establishes a high glucose microenvironment promoting the transcription of CD27, which is the T cell costimulatory molecule.…”
Section: Additional Chemical and External Treatmentsmentioning
confidence: 99%